The Role of Maternal Psychological Well-Being as a Predictor of Children’s Internalizing Behaviors (Jagannath University Journal of Life and Earth Sciences, 2024)
Nowadays, mothers' psychological well-being and behavioral outcomes in children have become a major topic of interest globally in the social and clinical arena. Though fathers play an important role in parenting, mothers are the key persons responsible for caring for their children. Thus, the present study investigated the relationship between maternal psychological well-being and their children's internalizing behaviors. This study also aimed to build up some models related to predictor and outcome variables based on the current research findings. A cross-sectional survey research design was employed to conduct the study on 800 participants (400 children and 400 mothers). The children were selected from ten Bangla medium high schools in Dhaka, and the age ranges of the children ranged from 11 to 13 years. The schools and the children were selected following a multistage random sampling technique. The self-reported Bangla version of the Strengths and Difficulties Questionnaire (SDQ), the Bangla version of the General Health Questionnaire (GHQ-28), and a Personal Information Form (PIF) were administered to the participants to collect data. The correlation analysis showed a significant positive correlation between maternal psychological well-being and children's internalizing behavior. Results also revealed that somatic symptoms, anxiety and insomnia, social dysfunction, and severe depression in mothers were significantly correlated with the internalizing behavior of children. Findings from multiple regression analysis indicated that the most powerful predictor of internalizing behavior was mothers' anxiety and insomnia, which independently explained 35% of the variance. The other significant predictors were social dysfunction, severe depression, and somatic symptoms. All four predictors jointly explained 40.6% of the variance in children's internalizing behavior. The implications of the findings have been discussed in light of theory and research evidence from earlier research.Jagannath University Journal of Life and Earth Sciences, 9(1): 45–56, 2023 (June)